Process-based modeling of soil nitrous oxide emissions from United States corn fields under different management and climate scenarios coupled with evaluation using regional estimates - Xia, Yushu; Wander, Michelle M.; Quiring, Steven M.; Yuan, Shanshui; Kwon, Hoyoung (Frontiers in Environmental Science, 2022)
Direct emissions of soil nitrous oxide during a growing season (N2Ogs) can be quantified with process-based models considering interactions between management, climate, and soil moisture when key data are available. We used an adapted “parameterized CENTURY/DAYCENT-model” (pCENTURY) calibrated with crop growth and soil organic matter decay coefficients at the county-level for the estimation of N2Ogs in the United States Corn Belt. Model estimated N2O-emissions from corn-based biofuels scenarios considering crop rotation, fertilizer inputs, tillage, and weather were compared against meta-summary of field observations from 55 studies. Both model and meta-summary ranked N2Ogs-emissions to be corn > wheat > soybean phase while model likely underestimated cover crop N2Ogs-emissions. The N2Ogs-emissions and the associated emission factors (EFs) were modeled and summarized to be greater after anhydrous ammonia than urea application and from conventional tilled than non-tilled fields. Modeled and observed N2Ogs-emissions after organic and inorganic fertilizer amendment did not differ due to high variability associated with the treatments. However, the organic fertilizer associated EFs were greater according to meta-summary data because of N input rates. Regionalized weather scenarios indicate hotspots for N2Ogs-emissions can occur where crop N uptake is limited during dry years and in eastern states also during normal or wet seasons. The pCENTURY-derived N2Ogs EFs (0.91 ± 0.19%) for counties investigated were only slightly lower than literature (1.07 ± 0.57%) or Tier-1 (1%) values. Our preliminary evaluation of regional soil moisture estimates showed reasonable agreement between monthly soil moisture estimates and the North American Soil Moisture Dataset during the growing season, but overestimation of soil moisture in winter-spring can influence the estimates of annual N2O emissions so future work is needed to calibrate soil moisture-associated model parameters. Our work provided scenario-based estimates of climate and management impacts on soil N2Ogs-emissions together with valuable spatial insights into EFs that will be improved by more accurate information of fertilizer inputs and more temporally refined model evaluation.